A pendant peptide endows a sunscreen with water-resistance. Issue 39 (26th September 2018) - Ellison, Aubrey J.; Raines, Ronald T.
Abstract : A small-molecule UV-filter with a pendant collagen mimetic peptide anneals to a collagen-laden surface and protects against UV radiation. Abstract : Ultraviolet light causes skin cancer. Salicylic acid and other molecular filters absorb damaging radiation but are washed away readily. Conjugation to a collagen mimetic peptide is shown to retain salicylic acid on collagen-containing skin surrogates after repeated washing. This strategy, which is highly modular, could enhance the water-resistance of sunscreens.